Analisis Proses Produksi Gasket di PT. Mitramas Muda Mandiri Karawang - Syamsi Dhuha; Sukanta Sukanta; Wahyudin Wahyudin (Peneliti.net, 2023)
Research conducted at PT. Mitramas Muda Mandiri in Karawang, West Java-Indonesia, which produces gaskets and fabrication. The purpose of this research is to describe the gasket production process at PT. Mitramas Muda Mandiri Karawang. This research utilizes a qualitative descriptive method by using a comparative analysis between theory and practice with the aim of analyzing each data collected and then drawing conclusions. Data collection techniques apply observation techniques and interview techniques. The results of the analysis show that PT. Mitramas Muda Mandiri in producing gaskets uses several stages including: blanking the workpiece, bending the workpiece, pressing the workpiece, spraying the workpiece, and packaging gaskets.